Prevalência e contexto genético de 16S rRNA metiltransferases em bacilos gram-negativos isolados no complexo Hospital São Paulo - Corsi, Dandara Cassu [UNIFESP] (2016)
The aminoglycosides have been inscreasingly used in the tretatment of infection caused by resistant bacteria to other classes of antimicrobials. The production of 16S rRNA metyltransferases has been a cause of concern, because they are responsible for high level of resistance to this antimicrobial class, and limiting the tereapeutic options. Objective: The aim of this study was to characterize the presence of genes encoding for 16S rRNA metyltransferases. Methodology: Were recovered all gram-negatives isolated from the Complex Hospital São Paulo/UNIFESP from October to December of 2014.The isolates with a reduced susceptible profile to aminoglycosides by Phoenix or manual techniques were selected for confirmation of susceptibility profile by agar screening by testing amikacin, gentamicin, and tobramicin according to the CLSI guidelines (2015). The presence of genes encoding for 16 rRNA methyltransferases was verified by PCR. Antimicrobial susceptibility profile of isolates possessing 16 rRNA methyltransferases genes was determined by CLSI broth microdilution. Evaluation of genetic similarity of the 16S rRNA methyltransferases isolates was determined by PFGE. Because of the spread of a single clone, only two isolates were evaluated by the MLST. Conjugation and transformation tests were performed in this study. Three plasmids extracted from three isolates [two K. pneumoniae (carrying blaKPC-2 and not carrying blaKPC-2) and a single isolate of P. mirabilis carrying rmtB gene] were sequenced. Results: Among 1248 consecutives isolates, 55 were resistant to the three aminoglycosides tested, in which 22 K. pneumoniae and one P.mirabilis carried rmtB, and four P. aeruginosa possessed rmtD. These isolates showed MICs >128 uL/mL to aminoglycosides. Only one isolate of K. pneumoniae (A64.216) and isolate of P. mirabilis (64.421) were susceptible to most carbapenems. The isolates carrying rmtB were also positive for blaCTX-M-1/2, blaSHV, blaTEM. However, only 6 strains carried blaCTX-M-14. Only two isolates did not encode blaKPC-2 (one isolate of K. pneumoniae-A64.216 and P. mirabilis isolate). The blaSPM-1 gene was identified in all P. aeruginosa possessing rmtD, which exhibited a single PFGE pattern. A single PFGE pattern was observed among K. pneumoniae isolates possessing rmtB, that were classified under ST258. No transconjugants ou transformants were obtained. According to the plasmid DNA sequencing, it was observed that rmtB-1 gene was inserted into transposon, which was flanked by blaTEM-1, and a class1 integron. blaKPC-2 and rmtB- 1 gene were inserted into distinct plasmids in isolated K. pneumoniae A64.477. blaCTX-M-14 gene was inserted in the same plasmid that carried rmtB-1 in the P. mirabilis strain. Conclusions: The prevalence genes encoding 16S rRNA methyltransferases was low among gram- negatives isolated from the Complex Hospital São Paulo. The sequencing of plasmids showed the location and context which is inserted the rmtB-1 gene and the location of other resistance and virulence, as well as replication and transfer genes. The K. pneumoniae plasmids were classified as IncFIIk. The P. mirabilis plasmid was considered as non-typeable and the plasmid blaKPC-2 harboring showed an uncertain result.